Data and Applications Security and Privacy XXX 30th Annual IFIP WG 11.3 Conference, DBSec 2016, Trento, Italy, July 18-20, 2016. Proceedings - Ranise, Silvio; Swarup, Vipin (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the refereed proceedings of the 30th Annual IFIP WG 11.3 International Working Conference on Data and Applications Security and Privacy, DBSec 2016, held in trento, Itlay, in July 2016. The 17 full papers and 7 short papers presented were carefully reviewed and selected from 54 submissions. Their topics cover a wide range of data and application security and privacy problems including those of mobile devices, collaborative systems, databases, big data, virtual systems, cloud computing, and social networks. The program also included two invited talks.